Plate fixation in periprosthetic femur fractures Vancouver type B1: preliminary report of macroscopic evaluation of the cement mantle and short literature review - Bibiano, Luigi; Stamboltsyan, Grigor; Touloupakis, Georgios; Ghirardelli, Stefano; Biancardi, Elena; Longo, Giuseppe Edoardo Giovanni; Antonini, Guido; Crippa, Cornelio (Acta Biomedica Atenei Parmensis, 2019)
he goal of our preliminary report is to investigate hip stem stability and intra-operative cement mantle integrity after screw insertion in plate fixation of periprosthetic Vancouver B1 femur fractures. From a cohort of 50 patients with a periprosthetic femur fracture treated in our department from February 2012 until February 2017, we included in our study patients with a periprostethic Vancouver B1 femoral fracture in cemented hip arthroplasty and hemiarthroplasty, operated with ORIF using a 4.5/5.0 LCP Proximal Femoral Hook Plate ® (Synthes, Switzerland) with at least one screw perforating the cement mantle. Anteroposterior and lateral femur views and pelvis X-rays were performed preoperatively. The stability of the hip implant and the cemented mantle integrity was evaluated intra-operatively in a macroscopic way and with a post-operative X-ray in anteroposterior and lateral views. Only 7 patients satisfied the inclusion criteria; no lesion/break of the cement mantle occurred intra-operatively at any step during drilling or screw insertion, also confirmed with C-arm assessment. No cases of stem mobilization were found and cement mantle integrity was maintained in every case. Insertion of screws around a cemented stem for plate fixation in periprosthetic femur fractures Vancouver type B1 could be considered a safe procedure. However, further and more extended studies are necessary for proving additional knowledge at the evaluation of the cement mantle in osteosynthesis procedures.